Large animal models for the study of tendinopathy - Zhang, Guorong; Zhou, Xuyan; Hu, Shuang; Jin, Ye; Qiu, Zhidong (Frontiers in Cell and Developmental Biology, 2022)
Tendinopathy has a high incidence in athletes and the aging population. It can cause pain and movement disorders, and is one of the most difficult problems in orthopedics. Animal models of tendinopathy provide potentially efficient and effective means to develop understanding of human tendinopathy and its underlying pathological mechanisms and treatments. The selection of preclinical models is essential to ensure the successful translation of effective and innovative treatments into clinical practice. Large animals can be used in both micro- and macro-level research owing to their similarity to humans in size, structure, and function. This article reviews the application of large animal models in tendinopathy regarding injuries to four tendons: rotator cuff, patellar ligament, Achilles tendon, and flexor tendon. The advantages and disadvantages of studying tendinopathy with large animal models are summarized. It is hoped that, with further development of animal models of tendinopathy, new strategies for the prevention and treatment of tendinopathy in humans will be developed.